-35+5-(+6)-(-13) qual è a resolução
Soluções para a tarefa
Respondido por
1
-35+5-(6)-(-13) =
-30 - 6 + 13 =
-36 +13 =
13 - 36 =
-23
Espero ter ajudado!
-30 - 6 + 13 =
-36 +13 =
13 - 36 =
-23
Espero ter ajudado!
Respondido por
1
Olá,
Vamos lá,
=-35+5-(+6)-(-13)
=-35+5-6+13
= -23
Resposta: -23
Vamos lá,
=-35+5-(+6)-(-13)
=-35+5-6+13
= -23
Resposta: -23
MISSÃO DO BRAINLY: - Mudar a cara da educação no Brasil.
Perguntas interessantes
ENEM,
11 meses atrás
Matemática,
11 meses atrás
Português,
1 ano atrás
Física,
1 ano atrás
Inglês,
1 ano atrás
Matemática,
1 ano atrás